Mapping and monitoring building decay patterns by photomodelling based 3D models - Mariella De Fino; Rosella Alessia Galantucci; Fabio Fatiguso (Tema, 2019)
A framework is presented for the evaluation and diagnosis of the state of conservation of the built heritage, based on the use of virtual immersive environments and three-dimensional models, as essential tools for the analysis and correlation of diagnostic data. Thus, some early studies are presented on the application of image processing routines that might extract from the point clouds some relevant information toward the semi-automated control of cracking patterns and surface alterations in heritage buildings.